2020
DOI: 10.1002/cjp2.183
|View full text |Cite
|
Sign up to set email alerts
|

Mixed large cell neuroendocrine carcinoma and squamous cell carcinoma of the colon: detailed molecular characterisation of two cases indicates a distinct colorectal cancer entity

Abstract: We present two rare cases of mixed large cell neuroendocrine carcinoma and squamous cell carcinoma of the colon. A literature search revealed only three published cases with similar histology but none of these reports provided profound molecular and mutational analyses. Our two cases exhibited a distinct, colon-like immunophenotype with strong nuclear CDX2 and β-catenin expression in more than 90% of the tumour cells of both components. We analysed the two carcinomas regarding microsatellite stability, RAS, BR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Previously, only six cases of MiNENs with SCC component have been described in the colorectum [ 1 , 5 8 ], and only one tumor was histologically covered by tubulovillous adenoma like ours [ 7 ]. It is currently hypothesized that the adenocarcinoma component and NEC component of mixed adenoneuroendocrine carcinoma (MANEC, a subgroup of MiNEN [ 3 ]) arise from either multipotent stem cells or 2 similar but separate precursors.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Previously, only six cases of MiNENs with SCC component have been described in the colorectum [ 1 , 5 8 ], and only one tumor was histologically covered by tubulovillous adenoma like ours [ 7 ]. It is currently hypothesized that the adenocarcinoma component and NEC component of mixed adenoneuroendocrine carcinoma (MANEC, a subgroup of MiNEN [ 3 ]) arise from either multipotent stem cells or 2 similar but separate precursors.…”
Section: Discussionmentioning
confidence: 84%
“…Possible causes for squamous colonic carcinoma are malignant transformation of persistent ectopic embryonal nests of ectodermal cells, chronic inflammation, human papillomavirus, pelvic radiation exposure, etc. [ 1 , 2 ]. Some authors postulated that the non-neuroendocrine component might give rise to a neuroendocrine component through the trans-differentiation process and then acquire a more aggressive phenotype [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Munakata et al reported this rare case of colon cancer, although final pathologic examination suggested the primary lesion likely originated from the lung 26 . Conversely, Woischke et al present two cases of combined LCNEC and SCC of the colon with histologic and genetic evidence of local origin in the colon 27 . Furthermore, the authors present genetic evidence of mutations of the FBXW7 gene leading to upregulation of the Wnt‐signaling pathway, a possible pathophysiologic explanation for local tumorigenesis of this rare combined malignancy.…”
Section: Discussionmentioning
confidence: 98%
“…Outside of the H&N, a small number of case reports in the literature describe combined LCNEC and SCC in the gastrointestinal tract, specifically in the colon and rectum 26–29 26 .…”
Section: Discussionmentioning
confidence: 99%